Free amino acids in amniotic fluid of pregnant women at term 50 - Harrison, Jack (2015)
The main biochemical aspect fetal growth will be given mainly for the synthesis of protein structures from free via placental circulation or through ingestion of amniotic fluid by the fetus amino acids. In order to contribute in this respect, the present work shows the results obtained to determine the free amino acids in amniotic fluid of 50 pregnant women 39-41 weeks transvaginal obtained by amniocentesis at the time of delivery and using the technique exchange chromatography ion having identified 19 amino acids that showed marked variation between the values of each sample over the same amino acid.